An energy optimized routing algorithm for IoT-enabled WSN - Sheth S.D.; Verma Y.; Kaur G.; Chanak P. (My University, 2025)
Nowadays, the Internet of Things (IoT) has gained significant importance. The Wireless Sensor Networks (WSNs) is a subset of IoT that is used as a major data-gathering component of any IoT-based system. An energy-efficient routing scheme is very important for resource-constraint IoT-enabled WSNs that can effectively improve the network lifetime and performance of the network. The existing routing scheme does not consider the battery limitation and successful packet delivery. The proposed scheme provides an energy-efficient solution through the meta-heuristic algorithm of modified firefly to perform routing within the networks. The results show that the proposed scheme outperforms compared to state-of-the-art algorithms in terms of different network parameters such as network lifetime, average residual energy, and the number of packets delivered to the base station. © 2021 IEEE.